Motivation towards employee’s commitment at SAJ Holdings Sdn.Bhd / Noor Azilla Ja’afar and Nor Ellyani Johari - Ja’afar, Noor Azilla; Johari, Nor Ellyani (Faculty of Business and Management, 2013)
This quantitative research aims to examine the impact of motivation through job involvement, working environment and incentives that influence on employees’ commitment. This includes the objectives as follows, which are to determine the relationship between Job Involvement and the Employee’s commitment, to determine the relationship between Working Environment and the Employee’s commitment, to determine the relationship between Incentives and Employee’s Commitment and to identify the most influential factors that impact of motivation on employee’s commitment. According to the theory by Allen and Meyer (1997) as well as past literatures were used to support the research hypotheses. Survey data was collected from 85 employees through convenience sampling of among nonexecutive staffs at SAJ Holdings Sdn. Bhd (Kluang Branch). SPSS version 20 was used to analyse the data. The reliability test was conducted using Cronbach Alpha and data was analysed using descriptive statistics such as frequency distribution and inferential statistics, namely Pearson Correlation, Multiple Regression, ANOVA and Co-efficient. The Pearson Correlation Analysis revealed that: (1) There is a very strong and positive significant relationship between job involvement and employees’ commitment (r = 0.635) (2) There is a moderate and positive significant relationship between working environment and employees ‘commitment (r = 0.529) and (3) There is a moderate and positive significant relationship between incentives and employees’ commitment (r = 0.491). The Adjusted R Square of 0.603from Multiple Regression Analysis shows that 60.3% of employees’ commitment can be explained by job involvement, working environment and incentives. The multiple regression analysis also shows that job involvement is the strongest predictor of employees ‘commitment with Beta Co-efficient of0.407 respectively. Limitations, implications and suggestions are also discussed.